THE EFFECTS OF ACTIVITY – BASED LEARNING PROGRAM ON MATHEMATICS CREATIVE THINKING AMONG SEVENTH GRADE STUDENTS - Aromrit, Umaporn; Kambhu Na Ayudhaya, Paradee; Aeamtassana, Thammachot (Journal of Education and Innovation, 2025)
This study aims to (1) develop an activity-based learning management program to enhance mathematical creativity among Grade 7 students, and (2) investigate the effects of the program on the mathematical creativity of Grade 7 students. The research population consisted of 452 Grade 7 students from 12 classrooms at Triam Udom Suksa Nomklao School in the academic year 2024. The sample comprised 40 Grade 7 students whose scores on a mathematical creativity assessment were below the 25th percentile. The sample was randomly divided into an experimental group and a control group, each consisting of 20 students. The experimental group participated in the activity-based learning management program to enhance mathematical creativity outside regular class hours, while the control group did not participate in the program. The research instruments included a mathematical creativity assessment and an activity-based learning management program designed to enhance mathematical creativity among Grade 7 students. The research findings were as follows (1) The activity-based learning management program for enhancing mathematical creativity consisted of a series of activities employing an activity-based approach aimed at developing students’ mathematical creativity. The program focused on three components of mathematical creativity: fluency, flexibility, and originality. The program included four steps. Step 1: Introduction The teacher explained the lessons and activities, clarified the roles and responsibilities of students, and prepared them for learning, such as by reviewing prior knowledge. Step 2: Activity The teacher divided students into groups and facilitated the activities, providing support as needed. Step 3: Reflection Students reflected on the knowledge and insights gained from participating in the activities. Step 4: Evaluation Learning outcomes were evaluated based on the activities through self-assessment, peer assessment, and teacher assessment, with feedback used to improve future learning management. (2) The results showed that students in the experimental group who participated in the program had significantly higher post-program scores on mathematical creativity compared to their pre-program scores at the .05 significance level. Additionally, the experimental group had significantly higher average scores on mathematical creativity than the control group, also at the .05 significance level.